1989
DOI: 10.2166/nh.1989.0011
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Relationship between the Hydraulic Conductivity and Primary Sedimentary Structures of Till

Abstract: An investigation has been made of the relationships between saturated hydraulic conductivity, porosity and micro-structure of undisturbed lodgement till samples. 35 measurements with a constant head laboratory permeameter are the basis for the discussion. All the measurements were made on undisturbed till samples. In order to minimize the effects of soil forming processes and to have the most homogeneous conditions all sampling were made from the C-horizon. The samples have a size of about 300 cm3. Porosity da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Haldorsen et al (1983) found that the hydraulic conductivity of some till units is controlled more by structural properties such as sorted sediment zones and fractures than by grain size distribution. Nyborg (1989Nyborg ( , 1990 measured the hydraulic conductivity of 35 oriented samples of till taken from a drumlin in western Sweden using a permeameter. He determined the hydraulic conductivity of small (about 300 cm3) samples and found a statistical association between grain orientation and hydraulic conductivity.…”
Section: Background Hydrogeological Studies Of Tillmentioning
confidence: 99%
“…Haldorsen et al (1983) found that the hydraulic conductivity of some till units is controlled more by structural properties such as sorted sediment zones and fractures than by grain size distribution. Nyborg (1989Nyborg ( , 1990 measured the hydraulic conductivity of 35 oriented samples of till taken from a drumlin in western Sweden using a permeameter. He determined the hydraulic conductivity of small (about 300 cm3) samples and found a statistical association between grain orientation and hydraulic conductivity.…”
Section: Background Hydrogeological Studies Of Tillmentioning
confidence: 99%
“…Hart, 1994; Benn, 1995; Hooke and Iverson, 1995; Truffer and others, 2000), and studies of till microfabric provide information about this process. Microfabrics defined by elongate clay and sand particles in tills have been studied by Harrison (1957), Gravenor and Meneley (1958), Ostry and Deane (1963), Evensen (1971), Kujansuu (1976), Johnson (1983) and Nyborg (1989), among others. In some studies, microfabrics have been used as indicators of subglacial deformation (Menzies and Maltman, 1992; Van der Meer, 1993; Menzies and others, 1997) or to differentiate till types (Van der Meer, 1990).…”
Section: Introductionmentioning
confidence: 99%